Fungal Endocarditis in a Preterm Neonate. Issue 2 (June 2021) - Mukherjee, Devdeep; Nayak, Hemant Kumar
Invasive fungal infections (IFIs) are an important cause of neonatal mortality and morbidity. A total of 5% of IFIs are complicated by fungal endocarditis. Mortality can be as high as 50%. We present a preterm, very low birth weight infant with infective endocarditis. Echocardiography showed a large pedunculated vegetation attached to the inferior vena cava and right atrium junction. Baby had Candida tropicalis in his blood cultures and was managed conservatively with antifungals. Surgery although planned was not possible considering baby being preterm with very low birth weight.